Mitochondria targeted nanoparticles for the treatment of mitochondrial dysfunction-associated brain disorders - Buck, Amy Claire; Maarman, Gerald J.; Dube, Admire; Bardien, Soraya (Frontiers in Bioengineering and Biotechnology, 2025)
Mitochondria play a significant role in several cellular activities and their function in health and disease has become an important area of research. Since the brain is a high-energy-demanding organ, it is particularly vulnerable to mitochondrial dysfunction. This has been implicated in several brain disorders including neurodegenerative, psychiatric and neurological disorders, e.g., Parkinson’s disease and schizophrenia. Significant efforts are underway to develop mitochondria-targeting pharmaceutical interventions. However, the complex mitochondrial membrane network restricts the entry of therapeutic compounds into the mitochondrial matrix. Nanoparticles (NPs) present a novel solution to this limitation, while also increasing the stability of the therapeutic moieties and improving their bioavailability. This article provides a detailed overview of studies that have investigated the treatment of mitochondrial dysfunction in brain disorders using either targeted or non-targeted NPs as drug delivery systems. All the NPs showed improved mitochondrial functioning including a reduction in reactive oxygen species (ROS) production, an improvement in overall mitochondrial respiration and a reversal of toxin-induced mitochondrial damage. However, the mitochondrial-targeted NPs showed an advantage over the non-targeted NPs as they were able to improve or rescue mitochondrial dynamics and biogenesis, and they required a lower concentration of the in vivo therapeutic dosage of the drug load to show an effect. Consequently, mitochondria-targeted NPs are a promising therapeutic approach. Future studies should exploit advances in nanotechnology, neuroscience and chemistry to design NPs that can cross the blood-brain barrier and selectively target dysfunctional mitochondria, to improve treatment outcomes.